A Buddhist Perspective on a Global Human Rights - Sallie B. King (Journal of Dharma, 1995)
There are two parts to this paper: (1) a response to Buddhist concerns about the notion of human rights; and (2) a discussion of the possibility of a global ethic from a Buddhist perspective. In these remarks I aspire to make a strong Buddhist case for the support of human rights and the articulation and endorsement of a global ethic in harmony with Buddhist principles.! I will take each of these points in turn.